SOCIAL AS SACRED DALAM PERSPEKTIF EMILE DURKHEM - Rijal Mahmud (TASÂMUH, 2018)
Society is a reality that is independent of individuals. The reality then forms the value of binding norms for each individual. From the results of the relationship or interaction that gave birth to the binding norm value, the community as an entity will gradually form a belief system or they believe in something that is not good. So, in fact, religion and society have a very close relationship, a living and developing religion and the reality of its adherents. While society naturally believes in a "sacred" concept which they consider to have supernatural powers. There are religions in his study, explaining that religion has a central position in primitive societies, its reality even though the "secret" nature is represented by different totems, but its essence has the same meaning